A ascensão dos métodos econométricos e sua influência na economia: o debate Keynes-Tinbergen e seu efeito na ciência econômica - Almeida, Rafael Galvão de (Universidade Federal de São Carlos, 2014)
This work had as its objective, by the means of a historic reconstruction of the history of econometrics, with emphasis on its business cycle models, to introduce the concept of performativity to the analysis of economic doctrines. The performativity argues that the line between theory and practice is thinner than it is thought, i. e., that in certain circumstances, the economic theory do not only describe the world, but it can influence it, it can make the agents change their behavior to conform to its predictions. For this, using the Keynes-Tinbergen debate as a background, we sought for evidence that showed the performative effects of the adoption of econometric methods onto the canon of the economic theory, once that studies showed performative effects with models used in the financial market. We conclude that, by the evaluation of the debate, its conclusion made possible emerge an econometric theory that, consequentially, could have performative effects in the economy.
The ascension of econometric methods and theis influence in the economy: the Keynes-Tinbergen debate and its effect in economics
Keywords: Econometria; Keynes, John Maynard, 1883-1946; Tinbergen, Jan, 1903-1994; modelos; política econômica; John Maynard Keynes; Jan Tinbergen; economics; economy; econometrics; models; performativity; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::TEORIA ECONOMICA::HISTORIA DO PENSAMENTO ECONOMICO